Care strategies offered to families of children with Autism Spectrum Disorder in health services in Brazil: A scoping review (Research, Society and Development, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that manifests in early childhood and is characterized by deficits in communication and social interaction, as well as by restricted and repetitive patterns of behavior, interests, or activities. The challenges in managing the symptoms and the scarcity of services for this population necessitate greater dedication to the care of the child, leading to emotional and physical strain on other family members. Shared care, information exchange, and strengthening the social and support network for the family can mitigate the impacts of ASD. Objective: This study aimed to map the care strategies provided to families of children with ASD in healthcare services in Brazil. Method: This is a scope review based on the Joanna Briggs Institute, conducted using the Virtual Health Library and Scielo databases, including scientific articles in Portuguese published in national journals over the last ten years. Results: It was identified that the strategies implemented with the families of children with ASD mostly occurred in the Child and Adolescent Psychosocial Care Centers. The most common strategies were therapeutic groups, support, individual care, and family guidance, developed in a multiprofessional manner. These actions facilitated the development of a social network among family members, the formation and strengthening of bonds between them and the team, coordination with the health network, family empowerment, and family participation as an agent in the child's treatment. The mother was the primary caregiver and the central point of contact with the team.Conclusion: The study revealed that the strategies led to the development and strengthening of bonds between participants and the health team, family empowerment, coordination between the network and service professionals, and access to rights for families and children with ASD. The need to consider gender perspective in implementing care strategies for families of children with ASD is highlighted.